Weeb Simp Behavior Among Vtubers Through Uses and Gratifications: Perilaku Weeb Simp di Kalangan VTuber Melalui Penggunaan dan Kepuasan - Maulana, Muhammad Rizky; Dharma, Ferry Adhi (House of Wisdom: Journal on Library and Information Sciences, 2025)
The phenomenon of simping among weebs towards VTubers is an intriguing topic to analyze through the lens of the Uses and Gratifications theory. This study aims to understand how VTuber fans fulfill their emotional, social, and identity needs through interactions with their virtual idols. Using a qualitative descriptive approach, this research conducted interviews with nine informants actively engaged in the VTuber fan community. The findings reveal four primary motivations driving attachment to VTubers: diversion, where VTubers serve as an escape from real-life pressures; personal relationships, which foster parasocial bonds that create a sense of emotional closeness; social identity, which strengthens a sense of belonging within fan communities; and surveillance, where fans actively seek information about VTubers to stay updated. These findings illustrate that VTubers are not merely a source of entertainment but also function as social agents that fulfill the psychological and emotional needs of their audience. Highlights:   VTubers serve as an emotional escape, providing diversion from real-life stress. Parasocial relationships foster emotional closeness and attachment among fans. Fans seek social identity and belonging within VTuber fan communities. Keywords: VTuber, Simp, Weebs